An event-triggered approach to finite-time observer-based control for Markov jump systems with repeated scalar nonlinearities. (June 2018) - Li, Jingyu; Shen, Liang; Yao, Fengqi; Zhao, Huanyu; Wang, Jing
This paper studies the issue of finite-time observer-based control via an event-triggered scheme for Markov jump repeated scalar nonlinear systems. An observer-based controller via an event-triggered scheme is proposed, which can save the limited network communication bandwidth effectively, so that the resulting error system is stochastically finite-time bounded. Based on the positive definite diagonally dominant matrix and the Lyapunov function technique, a sufficient condition is presented for the solvability of the addressed problem, and the desired observer-based controller can be constructed via a convex optimization problem. In the end, a simulation example is employed to show the validity and practicability of the proposed design method.